THE ECOLOGICAL MANAGEMENT OF OPERATION MODE FOR HEPS - Тімченко, В.М.; Тімченко, О.В.; Лахай, Ю.О.; Іванова, Н.О.; Кушнір, Н.І. (Science-based technologies, 2009)
Based on the analysis of modern researches, the ecological management of operation mode for HEPS is elabo-rated and proposed.